PENGARUH BIMBINGAN ORANG TUA TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA MATA PELAJARAN BAHASA ARAB MADRASAH TSANAWIYAH FATAHILLAH KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Eka Pertiwi (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
This research is to find out influence of parents attention againt student achievement through student motivation. This type of research was ex-post facto using quantitative approach. Instruments were used are scale and documentation. The research subject were Arabic Language Subject Madrasah Tsanawiyah Fatahillah District Jati Agung South Lampung District drawn by proportional random sampling. The research was analyzed by path analysis. The results show that parents attention has positve effect on student achievement through student motivation with regression line equation Y=44,02+0,05X+0,42Z, Fcount > Ftable (88,31 > 3,92) and Tcount > Ttable (4,00 > 1,98). The influence of parents' attention againt student achievement through student motivation by 60% with contribution of parents’ attention to student motivation by 0,35 and contribution of student motivation to student achievement by 0,42.